Women's Defense in Aceh Leadership Polemics: Ahmad At-Thayyib's Perspective on Women's Leadership Laws - Shori, Alam An (Proceeding of International Conference on Engineering, Technology, and Social Sciences (ICONETOS); Vol 4 No 1 (2024): Proceeding of International Conference on Engineering, Technology, and Social Science 2024, 2025)
This research is as a response to the polemic about the law of women's leadership in Aceh which is busy ahead of the 2024 regional head elections. It examined the reporting of serambinews.com in defence of women in response to the polemics over the prohibition of female leadership in Aceh. The purpose of the research is to examine the ideology found in serambinews.com's reporting, then the ideology found is studied based on the views of the Grand Sheikh of al-Azhar Egypt, Sheikh Ahmad at-Thayyib. This research is a critical qualitative research. The data collection techniques used are reading techniques and note-taking techniques. The data analysis technique uses Norman Fairclough's critical discourse analysis technique which consists of three dimensions, namely the text dimension, discursive practices, and socio-cultural practices. Then the results of the analysis were compared with the opinion of Sheikh Ahmad at-Thayyib who is the Grand Sheikh of al-Azhar on the law of women's leadership. Researchers found a discourse of defence of women in the news of the polemic of women's leadership in Aceh in terms of linguistics. In addition, it also found how the discourse was produced and consumed, as well as how the context behind the defence. The implications of this study highlight the role of media in shaping public perceptions and discourse on sensitive socio-religious issues, such as women's leadership. Additionally, the study emphasizes the importance of aligning media narratives with moderate religious perspectives, such as those of Sheikh Ahmad at-Thayyib, to promote balanced and progressive interpretations. This research contributes to the understanding of how critical discourse analysis can reveal deeper ideological currents in media and offers insights into the intersection of religion, gender, and media in shaping public opinion.